Extracellular vimentin is expressed at the rear of activated macrophage-like cells: Potential role in enhancement of migration and phagocytosis - Thalla, Divyendu Goud; Rajwar, Ashish Chand; Laurent, Annalena Maria; Becher, Johanna Elisabeth; Kainka, Lucina; Lautenschläger, Franziska (Frontiers in Cell and Developmental Biology, 2022)
Macrophages have a vital role in the immune system through elimination of cell debris and microorganisms by phagocytosis. The activation of macrophages by tumour necrosis factor-α induces expression of extracellular cell-surface vimentin and promotes release of this vimentin into the extracellular environment. Vimentin is a cytoskeletal protein that is primarily located in the cytoplasm of cells. However, under circumstances like injury, stress, senescence and activation, vimentin can be expressed on the extracellular cell surface, or it can be released into the extracellular space. The characteristics of this extracellular vimentin, and its implications for the functional role of macrophages and the mechanism of secretion remain unclear. Here, we demonstrate that vimentin is released mainly from the back of macrophage-like cells. This polarisation is strongly enhanced upon macrophage activation. One-dimensional patterned lines showed that extracellular cell-surface vimentin is localised primarily at the back of activated macrophage-like cells. Through two-dimensional migration and phagocytosis assays, we show that this extracellular vimentin enhances migration and phagocytosis of macrophage-like cells. We further show that this extracellular vimentin forms agglomerates on the cell surface, in contrast to its intracellular filamentous form, and that it is released into the extracellular space in the form of small fragments. Taken together, we provide new insights into the release of extracellular cell-surface vimentin and its implications for macrophage functionality.